CRISPR/CAS and interventions in the human genome: on nature and vice - Χασαπάκου (Dionysia Chasapakou) Διονυσία; Προϊκάκη (Stella Proikaki) Στέλλα; Μπόμπολα (Maria Bobola) Μαρία; Λάμπρου (George Lambrou) Γεώργιος (Bioethica, 2018)
Biological sciences are progressing rapidly. New methodologies of data analysis are necessary due to methods of production of mass biological data. However, new challenges have arisen concerning the knowledge management and its probable bioethical consequences on living beings. The next step in biological sciences’ advancement was the CRISPR/Cas9 method which made possible the selective genomic modification. This method is simple, effective and flexible and facilitates the genomic modification of any organism included human. It is the most impressive achievement on the path of constant advancement in biological engineering technology over the last decade. Although already widely applied in all species, it is its application on human beings that is most interesting. In literature, there is an intense debate and the new technologies are being compared to old eugenics, which gives a negative tone to these methods. On the other hand, there is the optimistic aspect which considers these methods as life-saving for human evolution. This paper aims to present and support the view that the moral value of things is not in nature but in user’s habit; to give grounds for more reflection, to discuss bioethical issues arising from the application of this technology and of course to highlight that whatever the upcoming developments of genomic are, they should foster and benefit the individual. Moreover, it is essential that the scientific community is in a constant and continuous consultation with society at large. Finally, new policies and updated guidelines are of utter importance in order to ensure the respect of human existence.